How to minimize risks for athletes during cold exposure - Burruss, P.; Rundell, K.; Castellani, J.; Snyder, A. (Spotlight on youth sports, 2002)
Winter weather poses a risk to young athletes, particularly those that exercise or compete out of doors. The following article was made available by the Gatorade Sports Science Institute and explains how coaches can minimize the risk for athletes during cold exposure. The following questions are answered: 1. What are the physiological and psychological responses to cold exposure that coaches and athletic trainers should keep in mind? 2. Can acclimatization occur with training in the cold? 3. Are any athletic injuries more prevalent during cold-weather exercise? 4. What practical steps should coaches and athletes take when preparing for training and competition in the cold?